Statistical analysis of the impact of micro- and macroenvironment factors on the sales of infant formula - Prykhodko, K. R.; Fataliieva, A.-N. Ya. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The objective of the article is to study the infant formula market in Ukraine and model the sales at this market, by case of breast milk substitutes (BMS) for babies younger than six months, to reveal the factors with impact on the sales. The study is made on official statistical data from the State Statistics Service of Ukraine, and data extracted from the AC Nielsen database. The regression model is constructed using the data from December 2011 to March 2016. The factors with theoretical impact on the sales of infant formula were chosen using the qualitative analysis: the factors of macro-environment (consumer price index, utility price index, consumer trust index, real disposable income, and number of children born), and the factors of micro-environment (price per unit, stock cover, numeric distribution, weighted distribution, size of portion). At the phase of quantitative analysis, the peculiarities of correlation-regression analysis of time series were taken into account: verification of the factors for the presence of multicollinearity, analytical alignment of time series, selection of significant factors and construction of a statistically significant model. The analysis shows that only two of the micro-environment factors had the significant impact on the sales of BMS: unit price and stock cover; and only one of the macro-environment factors had the significant impact: number of children born. As the constructed model has reliable statistical characteristics, the estimates produced by it have the sufficiently high accuracy and can be used by business entities in strategy building and quick reactions on the changing business environment.